2010
DOI: 10.4102/sajhrm.v8i1.225
|View full text |Cite
|
Sign up to set email alerts
|

HR competencies at a merged Higher Education Institution

Abstract: Orientation: Certain human resource (HR) competencies are essential to assist with the dynamics of change in the higher education landscape.research purposes: The aim of this study was to determine the HR competencies at a merged higher education institution. Other objectives were to establish the satisfaction of academics, administrative staff and management regarding the HR competencies and the importance thereof.Motivation for the study: Human resource professionals require assistance by providing HR compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
3
6
0
Order By: Relevance
“…More specifically, HR practitioners are limited in applying innovation, talent management, HR metrics, and HR business knowledge. These results concur with those of previous studies which found that HR professionals are still not allowed to play a strategic role in South African organisations and, as a result, HR competencies and practices are poorly applied (see Barkhuizen, 2015;Schultz, 2010;van Wyk, 2006;Walters, 2006). These findings are concerning, given that the respondents ranked all the measured HR competencies as important.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…More specifically, HR practitioners are limited in applying innovation, talent management, HR metrics, and HR business knowledge. These results concur with those of previous studies which found that HR professionals are still not allowed to play a strategic role in South African organisations and, as a result, HR competencies and practices are poorly applied (see Barkhuizen, 2015;Schultz, 2010;van Wyk, 2006;Walters, 2006). These findings are concerning, given that the respondents ranked all the measured HR competencies as important.…”
Section: Discussionsupporting
confidence: 82%
“…Schultz (2010) found that the HR department in a merged South African higher education institution displayed poor personal skills, HR business knowledge, and management skills. A study by van Wyk (2006) highlighted the lack of sufficient business knowledge among HR practitioners regarding a social responsibility issue such as HIV and AIDS.…”
Section: Literature Review Human Research Management Role and Competementioning
confidence: 99%
“…HR Business Knowledge, interpersonal skills and communication, HR solutions and implementation and HR risk emerged as the most important HR competencies. These results amplified the need for core HR competencies in an unstable business environment (Schultz, 2010;Ulrich et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Most of these organisations realise that their competitive advantage lies within their employees (Cascio & Boudreau, 2008;Chabault, Hulin, & Soparnot, 2012;Collings & Mellahi, 2009;Kaye & Smith, 2012). Worldwide socio-economic developments such as globalisation, increasing speed towards a service economy, shorter product life cycles, changes in workforce demographics, a focus on customer loyalty, the increasing 'war for talent, and an emphasis on financial performance challenge the human resources (HR) function in its role of creating added value for the organisation (Mamman & Sumantri, 2014;Schultz, 2010;Srimannarayana, 2010;Story, Barbuto, Luthans, & Bovaid, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation